Fidelity and betrayal under law. (2nd July 2016) - Cameron, Edwin
ABSTRACT: This is the text of the 2015 Bram Fischer Memorial Lecture, delivered at Rhodes House, Oxford, on 16 June 2015. These Memorial Lectures honour Bram Fischer QC, a South African lawyer who defended Nelson Mandela and other leaders of the liberation movement when on trial for their lives, and who himself died in imprisonment in 1975. The 2015 Lecture discusses Fischer's moral heroism, but also the compromises he made as a result of his involvement in an unjust legal system. It concludes by reflecting on Fischer's dissent against that system, and against the Afrikaner establishment of which he was part, and the lessons this has for us today. The Lecture is reproduced here with the kind permission of its organisers, Lord Joel Joffe and Prof Nic Cheeseman, and appears as it was delivered, with only minor editorial changes.